Coupled fixed point theorems for a ϕ-contractive mapping in partial metric spaces - Phakdi Charoensawan (2018)
© 2014 Phakdi Charoensawan. In this work, we prove some coupled fixed point theory for ψ-contractive in partial metric spaces which extend and generalize some results on fixed point theorems in ordered partial metric spaces. We also provide an example in support of our main result.